Pengaruh Kependudukan, Perekonomian Regional, dan Pembangunan Manusia terhadap Lingkungan: Tantangan dan Peluang bagi Pembangunan Kota Berkelanjutan - Arya Radinsyah Fauzi; Farid Azfa Putra; Ridho Alfajar; M Firman Afdallah; Vitriyani Tri Purwaningsih; Neli Aida (Diponegoro Journal of Economics, 2025)
This study examines the environmental effects of urban development by analyzing the influence of population, regional economy, and human development on waste generation in Sumatra, Indonesia. Using panel data from 10 provincial capitals and applying the generalized least squares (GLS) method, the study finds that population density and Gross Regional Domestic Product (GRDP) based on expenditure—a proxy for consumption levels—are positively associated with increased waste production. In contrast, the Human Development Index (HDI) exhibits a negative relationship with waste generation. The study contributes to the literature by employing a panel-data approach to explore the interplay between human development and waste production in urban Sumatra, offering insights for sustainable urban planning.